Aspetti del modernismo fascista (Italia, Francia, Germania: 1918-1939) (ENTHYMEMA, 2022)
Fascist culture is often associated with an anti-modernist attitude. Actually, as this article aims at demonstrating, modernist topics constantly cross far right-wing culture in Italy, as well as in France and in Germany. With respect to the by now canonical book of Roger Griffin (Modernism and Fascism, 2007), this article does not analyze the myth of the ethnic-national ‘regeneration’ (myth that, I believe, is present also in fascist anti-modernist perspectives), but it focuses in particular on the cultural glorification of industry and technology, and then on the reconciliation of art with the industrial scenario. Through a wide recon of the French, German, and Italian cultural milieu, this article offers to the reader a first mapping concerning the complex relation between modernism and fascist culture.
Keywords: Fascism; Modernism; Technology; Industry; Myth